2016
DOI: 10.4103/2249-4863.201153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic insomnia in adult patients and its correlation with medical comorbidities

Abstract: Introduction:Insomnia is one of the common but neglected conditions seen in family practice with long term and serious effects on health of a patient. Family physicians have the responsibility of diagnosing and adequately treating this. This study was done to find the prevalence of chronic insomnia in adult patients visiting a family medicine outpatient department (OPD) in a hospital and to assess the risk factors and co morbidities associated with it.Materials and Methods:A cross-sectional study was done in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(196 citation statements)
references
References 18 publications
(15 reference statements)
8
155
1
4
Order By: Relevance
“…The above‐mentioned thesis may be confirmed based on epidemiological data of insomnia that varies greatly across studies conducted worldwide, ranging from 6% to 50% or even 60% of the general population . Recent studies show that insomnia negatively affects work performance, impairs decision‐making, decreases concentration, increases the risk of motor vehicle accidents, destroys relationships and reduces the QOL . It was also found that female sex, mental health problems and physical health problems could be associated with an increased prevalence of insomnia; however, there is a small number of epidemiologic studies focused at the relationship between pain and insomnia .…”
Section: Introductionmentioning
confidence: 92%
“…The above‐mentioned thesis may be confirmed based on epidemiological data of insomnia that varies greatly across studies conducted worldwide, ranging from 6% to 50% or even 60% of the general population . Recent studies show that insomnia negatively affects work performance, impairs decision‐making, decreases concentration, increases the risk of motor vehicle accidents, destroys relationships and reduces the QOL . It was also found that female sex, mental health problems and physical health problems could be associated with an increased prevalence of insomnia; however, there is a small number of epidemiologic studies focused at the relationship between pain and insomnia .…”
Section: Introductionmentioning
confidence: 92%
“…However, the specific relationship between depression and changes in circadian sleep rhythm are not completely clear, with several hypotheses related to disturbance in circadian, social and sleep rhythms alignment (e.g., the phase-shift, phase advance, and social rhythms hypotheses) (77). Fatigue and sleep disturbances are also commonly reported by individuals with diabetes, with a recent study showing that 50% of diabetes patients reported insomnia compared to 27% of patients without diabetes (78). Large prospective studies show that reduced self-reported sleep duration (<6 hrs) is related to an increased risk of T2D, and this increased risk appears to be due to heightened inflammation, insulin resistance, appetite and weight gain associated with sleep loss (79,80).…”
Section: Homeostatic Dysregulation: Inflammation Metabolism and Smentioning
confidence: 99%
“…It is common in older adults, females, and people with medical and mental ill health. 3 The present study was aimed at assessing the sleep quality of patients attending the outpatient department of a rural health centre in Kacheepuram, Tamilnadu.…”
mentioning
confidence: 99%